A Predicted Genetic Parameter for Body Weight and Body Size at Yearling Age of Male Bali cattle - Meidina Chaerunissa; V.M. Ani Nurgiartiningsih (Faculty of Animal Science, Universitas Brawijaya, 2022)
This research aimed to predicted the genetic parameter for body weight and body size, including body height, body length, and chest girth at yearling age of male Bali cattle in BPTU-HPT Denpasar, Bali. The materials used were 79 heads of male Bali at yearling age. The variables observed were body weight (BW), body height (BH), body length (BL), and chest girth (CG) recorded from 2016 to 2018. The body weight and body size data were analyzed to find out the mean, standard deviation, and coefficient of variation. Variance and co variance component were analyzed using Analyses of Variance and Covariance one way lay out un balanced design. The heritability and genetic correlation were calculated using the paternal half-sib correlation method. Results showed that the average of body weight, body height, body length, and chest girth were 129.72±13.73 kg, 102.91±4.27 cm, 94.32±5.54 cm, and 121.91±8.47 cm, respectively. The value of heritability estimation for body weight, body height, body length, and chest girth were 0.50±0.08, 0.46±0.07, 0.44±0.07, and 0.10±0.02, respectively. The genetic correlation between BW-BH, BW-BL, and BW-CG were categorized as moderate to a high value (0.67, 0.98, and 0.35, respectively). Breeding value for body weight and body height were both 50% positive value, and breeding value for body length and chest girth were 40% and 60% positive value, respectively. The rank correlation coefficient between rank based on BW-BH, BW-BL, and BW-CG were 0.31, 0.61, and -0.01, respectively. Based on the heritability value, genetic correlation, and rank correlation coefficient, body length could be used as selection criteria, which would give a response to improve body weight.